2022
DOI: 10.1038/s41531-022-00353-4
|View full text |Cite
|
Sign up to set email alerts
|

Waist circumference and risk of Parkinson’s disease

Abstract: Although many studies support the association of obesity with neurodegenerative diseases, such as Parkinson’s disease (PD), there are limited data regarding the association between abdominal obesity and PD, with mixed findings. The aim of this study was to examine the association of waist circumference (WC) with the risk of PD incidence. We retrospectively analyzed a large-scale nationwide cohort of 6,925,646 individuals aged ≥40 years who underwent the Korean National Health Screening during 2009. We performe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
3
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(4 citation statements)
references
References 43 publications
0
3
0
Order By: Relevance
“…The robust association of "central obesity" and "muscle strength" patterns with both neurodegenerative diseases and MRIbased brain aging biomarkers aligned with previous evidence from Mendelian randomization 9 and observational studies. 6,7,24,25 The inverse associations of "bone density" 12 (high vs low) and "fat-to-lean mass" 26 (moderate vs low) patterns with the clinical onset of neurodegenerative diseases partly collaborated with previous studies yet showed inconsistency or even contradiction with the subclinical outcomes of brain aging biomarkers. Such discrepancies suggest potential reverse causation in clinical outcomes, even after incorporating a 5-year or 10-year lag time.…”
Section: Discussionmentioning
confidence: 81%
“…The robust association of "central obesity" and "muscle strength" patterns with both neurodegenerative diseases and MRIbased brain aging biomarkers aligned with previous evidence from Mendelian randomization 9 and observational studies. 6,7,24,25 The inverse associations of "bone density" 12 (high vs low) and "fat-to-lean mass" 26 (moderate vs low) patterns with the clinical onset of neurodegenerative diseases partly collaborated with previous studies yet showed inconsistency or even contradiction with the subclinical outcomes of brain aging biomarkers. Such discrepancies suggest potential reverse causation in clinical outcomes, even after incorporating a 5-year or 10-year lag time.…”
Section: Discussionmentioning
confidence: 81%
“…Collectively, the data implicate diet-induced obesity as a contributing factor to mitochondrial Complex I dysfunction in the brain, and that early compensatory responses may include enhanced antioxidant defense as well as increased mitochondrial biogenesis signaling. These findings are critical, as they provide mechanistic insight into the clinical link between obesity and mitochondrial Complex I related neurodegenerative disorders (Picone et al, 2020;Park et al, 2022).…”
Section: Discussionmentioning
confidence: 99%
“…Lack of mitochondrial Complex I protein or function is a feature observed in an array of neurodegenerative disorders (Schapira et al, 1990;Navarro et al, 2009;Adav et al, 2019;Holper et al, 2019), including those associated with increased adiposity (Picone et al, 2020;Park et al, 2022). Yet, the cause of Complex I dysfunction has yet to be elucidated (Wang et al, 2022).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation